2011
DOI: 10.3748/wjg.v17.i7.938
|View full text |Cite
|
Sign up to set email alerts
|

Transplantation of microencapsulated umbilical-cord-blood-derived hepatic-like cells for treatment of hepatic failure

Abstract: Transplantation of microencapsulated hepatic-like cells derived from umbilical cord blood cells could preliminarily alleviate the symptoms of AHF rats.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 16 publications
0
11
0
Order By: Relevance
“…This would allow the delivery of large numbers of HLC, which may be able to provide immediate support to liver function. Indeed, a recent study showed that encapsulated HLC generated from umbilical cord blood cells and grafted into the peritoneal cavity was able to rescue rats with acute hepatic failure [53]. HLC derived from hAEC secrete some of the immunomodulatory factors produced by the parental cells, but soluble HLA-G was significantly lower [22].…”
Section: Properties Of Encapsulated Hepatocyte-like Cells 871mentioning
confidence: 99%
“…This would allow the delivery of large numbers of HLC, which may be able to provide immediate support to liver function. Indeed, a recent study showed that encapsulated HLC generated from umbilical cord blood cells and grafted into the peritoneal cavity was able to rescue rats with acute hepatic failure [53]. HLC derived from hAEC secrete some of the immunomodulatory factors produced by the parental cells, but soluble HLA-G was significantly lower [22].…”
Section: Properties Of Encapsulated Hepatocyte-like Cells 871mentioning
confidence: 99%
“…Moreover, hematologic parameters such as ALT, AST and total bilirubin were significantly different between encapsulated and non-encapsulated cells. In addition, after 1-2 weeks post-transplantation, the authors observed the presence of fibrous tissue surrounding microcapsules in the greater omentum [124].…”
Section: Umbilical Cord Blood-derived Mscsmentioning
confidence: 97%
“…Undifferentiated hAECs were transplanted in SCID/beige mice. Albumin, AFP, BSEP, CYPs and over 30 markers were analyzed by real time PCR [124] Human Amniotic epithelial cells [135] Abbreviations: FBS, fetal bovine serum; IGF-I,insulin growth factor-I; OSM, oncostatin M; AFP, α-fetoprotein; FGF, fibroblast growth factor; ITS, insulin-transferrin-sodium selenite; CK-18, cytokeratin-18; HepPar-1, hepatocyte-paraffin-1; CK-19, cytokeratin-19; AAT, α-1-antitrypsin; TAT, tyrosine aminotransferase; HNF-3β, hepatic nuclear factor-3 β; LDLR, receptor low density lipoprotein; G6P, glucose-6 phosphatase, EGF, endothelial growth factor, bFGF, basic fibroblast growth factor; CYP3A4, cytochrome P450 3A4 subunit; HNF-4α, hepatic nuclear factor-4α; G6PD, glucose-6-phosphate dehydrogenase; ; CYP1A1, cytochrome P450 1A1 subunit; CYP2B6, cytochrome P450 2B6, CYP1A2, cytochrome P450 1A2 subunit; CYP2C8, cytochrome P450 2C8; subunit; CYP2D6, cytochrome P450 2D6 subunit; CYP2C9, cytochrome P450 2C9; subunit CYP2C19, cytochrome P450 2C19 subunit; CYP2E1 cytochrome P450 2E1 subunit; AHR, Aromatic hydrocarbon receptor, PXR, pregnane × receptor; CAR, constitutive aldosterone receptor; MMP2, metalloproteineasi-2; MMP9, metalloproteineasi-9;TIMP-1,tissue inhibitor metalloproteinases-1; PDGF, platelet-derived growth factor; Il1 β, interleukin-1; Il-2, interleukine-2; IL-6, interleukin-6; Il-10,interleukine-10;Il-13, interleukine-13; INFγ ,interferone-γ ; TNFα, tumor necrosis factor-α; TGFβ1, transforming growth factor β1;ALT, alanine aminotransferase; TBIl, total bilirubin levels in serum; TO, tryptophan 2,3 dioxygenase; TPO, thrombopoietin; SCF, stem cell factor; Flt Zheng and co-workers [134] showed that AFSCs expressing IL-1Ra (interleukin-1 receptor antagonist) may improve fulminant hepatic failure (FHF) in an in vivo model. The authors showed that administration of cells prevented liver failure and increased animals survival.…”
Section: Amniotic Fluid Stem Cellsmentioning
confidence: 99%
“…Liver matrix bolstered the phenotype of hepatoblasts when used as a substrate in vitro compared to collagen I alone. Liver proteins including growth factors, adhesion molecules, and matrix collagens have been included in the encapsulation process to maintain the function of different liver cell types in vivo [137,138]. Further assays are required to distinguish which components of the liver matrix are the greatest contributors to cell viability and phenotype.…”
Section: Hepatocyte Injection and Encapsulationmentioning
confidence: 98%